2019
DOI: 10.1101/665208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pervasive Translation in Mycobacterium tuberculosis

Abstract: ORF boundaries in bacterial genomes have largely been drawn by gene prediction algorithms. These algorithms often fail to predict ORFs with non-canonical features. Recent developments in genome-scale mapping of translation have facilitated the empirical identification of ORFs. Here, we use ribosome profiling approaches to map initiating and elongating ribosomes in Mycobacterium tuberculosis. Thus, we identify over 1,000 novel ORFs, revealing that much of the genome encodes proteins in overlapping reading frame… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 80 publications
3
28
0
Order By: Relevance
“…Our data also provides biochemical evidence for a ~14 nt spacing between the P-site and the 3' boundary of the mycobacterial ribosome, which is in agreement with estimates obtained in the attenuated M. tuberculosis mc 2 7000 strain (Smith et al, 2019) and the distance found in E. coli (Woolstenhulme et al, 2015). This distance was obtained by 3' assignment of RPF reads (Woolstenhulme et al, 2015) which has been shown to be the best method for determining the position of the ribosome on the mRNA.…”
Section: Discussionsupporting
confidence: 88%
“…Our data also provides biochemical evidence for a ~14 nt spacing between the P-site and the 3' boundary of the mycobacterial ribosome, which is in agreement with estimates obtained in the attenuated M. tuberculosis mc 2 7000 strain (Smith et al, 2019) and the distance found in E. coli (Woolstenhulme et al, 2015). This distance was obtained by 3' assignment of RPF reads (Woolstenhulme et al, 2015) which has been shown to be the best method for determining the position of the ribosome on the mRNA.…”
Section: Discussionsupporting
confidence: 88%
“…Weaver et al (2019) found ribosome profiling evidence, including evidence specifically for translation initiation (using retapamulin), for nine antisense overlapping gene candidates in E. coli K12, also shown, combined with the data from Weaver et al, in Figure 1A. As reported in a recent pre-print, Smith et al (2019) found many overlapping ORFs in Mycobacterium tuberculosis associated with ribosomes using retapamulin. From 355 novel ORFs expressed in two replicates they report 241 overlapping and embedded in annotated genes, including both sense, and antisense overlaps, of which many were very short.…”
Section: Introduction the Many Functions Of Antisense Rnassupporting
confidence: 57%
“…A recent, currently unpublished, study in M. tuberculosis (Smith et al, 2019) has claimed that novel ORFs identified by ribosome profiling typically do not illustrate the strong codon bias evident in annotated mycobacterial genes and therefore cannot be expected to be functional. Given that many of these ORFs are situated in antisense to annotated genes, where the genetic code limits the possibilities for achieving optimal codon usage, this result is not surprising, and we suggest provides little evidence for the claim that they are nonfunctional.…”
Section: Evolution and Constraint In Antisense Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the specificity of the signals found in all NGS experiments needs to be assessed and differentiated from a potentially pervasive background translation, i.e., undirected binding of ribosomes to RNAs (Ingolia et al, 2014). It was reported that pervasive translation initiation sites in bacteria predominantly lead to short translation products with an uncertain functionality status (Smith et al, 2019). However, the metabolic cost of pervasive translation would be high and cells should be driven to minimize such costly side reactions.…”
Section: Introductionmentioning
confidence: 99%